Cook Islands : Assessment of the Supervision and Regulation of the Financial Sector Volume I-Review of Financial Sector Regulation and Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper reviews financial sector regulation and supervision in the Cook Islands (CI). The CI has taken a number of measures to strengthen its financial sector regulation. New legislation was passed for the regulation of banking activity, and a Financial Supervisory Commission (FSC) was established. A suite of antimoney laundering legislation was enacted in May 2003 with work ongoing in respect of legislation for combating the financing of terrorism. The new Banking Act and FSC Act provide a good basis for sound financial sector regulation.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet